Redshift-Dependence of the Cosmic Expansion Rate: A Data-Driven Analysis of Observational H(z) Measurements - Joshi, Kamal; Gyanwali, Gunanidhi (Journal of Advanced College of Engineering and Management, 2026)
Observational measurement of the Hubble parameter provides direct information about the expansion history of the Universe (Hubble, 1929; Weinberg, 2008). While most studies rely on fitting observational data specific cosmological models, complementary information can be obtained through direct, model independent data analysis (Seikel et al., 2021). In this work, observational Hubble parameter data are examined using a normalized expansion gradient that quantifies the relative change of the expansion rate across consecutive redshift intervals. This simple diagnostic approach allows local variability in the cosmic expansion history to be explored without invoking assumptions about the underlying cosmological model. The analysis reveals non-uniform behavior of the expansion rate across redshift, demonstrating that gradient based methods can serve as a useful exploratory tool for identifying redshift ranges of enhanced dynamical evolution in observational cosmology (Moresco et al., 2016).